Decolonial Pedagogies: Contributions to Contemporary Pedagogical Practices (Docentes 2.0 Journal, 2026)
In contemporary education, there is an urgent need to promote decolonial pedagogies capable of questioning and offering alternatives to practices still rooted in rigid, inflexible colonial models. The objective of this essay was to highlight the importance of decolonial pedagogies in current educational practices. This essay was framed within the inductive method under the humanist paradigm, with a qualitative, interpretive approach and a narrative design focused on a specific topic, thereby allowing a reflective and comprehensive examination of the educational phenomenon from multiple critical perspectives. Within this analytical framework, the contribution of Walsh is highlighted, who conceives of decolonial pedagogies as practices aimed at opening education to a plurality of knowledge systems, languages, and forms of learning, fostering educational relationships based on respect, critical interculturality, and the collective construction of knowledge. Furthermore, the category of "buen vivir" (good living) is incorporated as an ethical-political horizon that guides the collective aims of education toward a more just, supportive, and sustainable community life. In conclusion, decolonial pedagogies constitute an indispensable path to redefining contemporary education by promoting formative processes committed to diversity, emancipation, and social transformation.
Keywords: Decolonial pedagogies; pedagogical practices; good-living